Mechanical Design of Extended Chassis Frame for Defence Vehicle - Naik, P. A.; Kalai, D. M. (Asian Review of Mechanical Engineering, 2016)
Generally defence vehicles are considered has the roughed machines, they can withstand very harsh environment. The defence vehicles generally have all wheel drives which enable them to tread difficult terrain and these vehicles are made of high strength materials with high factor of safety. This project is focused to design and analysis of extended chassis frame for such a vehicle. The vehicle chosen in this project is an eight wheeled vehicle with all wheels drive system (8×8) which is connected to the engine through a low deferential gear box. There is a need of adding additional super structure (extra pay loads) on the same vehicle. Extending the present chassis with the help of reinforcement at right locations will be a very effective technique for wide variety of mounting applications. Thus using the extended chassis frame many mounting can be installed/mounted without considerable change in the overall design; this is also economical. This project work is focused on Re-design of chassis frame by extending it by 900 mm at rear, based on end user requirement to withstand the different super structure loads, the same structure will be statically analyzed by using Finite Element Analysis method to verify the reinforcement of chassis frame and also to study the dynamic characteristics. This work involves static and dynamic analysis to determine key characteristics of a truck chassis. The static characteristics include identifying location of high stress area and the dynamic characteristics of truck chassis such as the natural frequency and mode shape.